Criminological theory : assessing philosophical assumptions - Walsh, Anthony, 1941-
Criminologists can benefit from questioning the underlying assumptions upon which they rest their work. Philosophy has the ability to clarify our thoughts, inform us of why we think about things the way we do, solve contradictions in our thinking we never knew existed, and even dissolve some dichotomies we thought were cast in stone. One of those dichotomies is free will vs. determinism. Criminology must reckon with both free will and agency, as posited by some theories, and determinism, as posited by others-including the ever more influential fields of genetics and biosocial criminology. This title examines philosophical concepts such as these in the context of important criminological theories or issues that are foundational but not generally considered in the literature on this topic.